Pendampingan Penyusunan Pembukuan Sederhana Bagi UMKM Toko Kelontong Asep Kecamatan Bekasi Utara - Idel Eprianto; Triana Yuniati; Tutiek Yoganingsih; Ery Teguh Prasetyo (Jurnal Abdimas Ekonomi dan Bisnis, 2022)
The purpose of this service activity is to overcome one of the problems that often occur byMSME business actors, namely regarding the management of bookkeeping in MSMEs whichis realized through a simple bookkeeping assistance program. The method in this service iscarried out through providing material about the introduction of simple bookkeeping, providingan understanding of how to compile simple bookkeeping and accompanying bookkeepingpractices. The object of service is the Asep Grocery Store which is located at Marga MulyaVillage, North Bekasi District.The results in this service activity found that so far the practiceof simple bookkeeping in the Asep Grocery Store business was not continuous and not storedand there was no standard format. With this activity, it is hoped that business owners have anunderstanding of financial records and feel the benefits of the importance of bookkeeping.Suggestions for further service development can continue through the form of accounting andbookkeeping activities through information technology-based applications that are simple andeasy to understand by the owner. Keywords: MSME (Micro, Small, and Medium Enterprises), Bookkeeping Management,Simple Bookkeeping Assistance